Reproducibility of Optical Coherence Tomography Retinal Nerve Fiber Layer Thickness Measurements Before and After Pupil Dilation - Alizadeh, Yousef (Ophthalmic Research Center, 2014)
PURPOSE: To evaluate the intra- and interobserver reproducibility of peripapillary retinal nerve fiber layer (RNFL) thickness measurements before and after pupil dilation using spectral-domain optical coherence tomography (SD-OCT). METHODS: In this observational case series, 44 eyes of 44 healthy subjects were scanned by two trained operators on the same day, using Cirrus SD-OCT (Carl Zeiss Meditec, Dublin, CA, USA). Three scans were obtained before and after pupil dilation by each operator. Mean ± standard deviation (SD) and coefficient of variation (CV) were used for description of results and variation of measurements respectively. Intraclass correlation coefficients (ICC) and Bland-Altman plots were used to evaluate validation and limits of agreement. RESULTS: Overall, 23 female and 21 male subjects with mean age of 36.9±8.8 (range, 20 to 50) years were enrolled. Mean RNFL thickness before pupil dilation was 92.6±7.2 (CV, 7.8%) and 92.4±6.8 (CV, 7.4%) µm by operator one and two, respectively. After pupil dilation, mean RNFL thickness was 92.7±7.9 (CV, 8.5%) and 92.0±7.5 (CV=8.2%) µm by observer one and two, respectively. ICCs ranged from 0.900 to 0.996. Mean absolute error of the two operators was less than 4.1µm. There were no significant differences in quadrant thicknesses before and after dilation. Interestingly, mean signal strength was not significantly affected by pupil dilation. CONCLUSION: In normal subjects with clear media, peripapillary RNFL thickness measurements using Cirrus SD-OCT have high inter- and intraobserver reproducibility before and after pupil dilation. Pupil dilation may not be necessary in all subjects to obtain reproducible RNFL thickness measurements.